Synthesis and charecterization of Benzamide Metal Complexes - Jhaumeer-Laulloo, Sabina; G. Bhowon, Minu; Reddi, Karuna (Asian Journal of Chemistry, 2010)
A few metal complexes of 2,2'-dithiobisbenzamide (DTBA) were synthesized and characterised by analytical and spectroscopic techniques. The IR data suggest coordination through nitrogen rather than oxygen of the amide group. All these complexes were found to be more effective catalysts in the oxidation of benzyl alcohol to benzaldehyde compared to free ligands.